Project activity of charitable foundations as one of the ways to implement public initiatives of citizens - E. A. Sokolova; P. V. Zozulya; A. V. Zozulya (Вестник университета, 2025)
The objectives of the research are the analysis of project activities of charitable foundations as one of the ways to implement public initiatives of citizens. The project activity concept has been disclosed, a number of its peculiarities have been considered. Since project activity in Russia is widely used in various spheres and industries, the charity features, its role in modern society, and manifestation forms have been studied. To date, charitable activity in Russia is carried out for the purpose of social support and protection of citizens, preparing the population to overcome the consequences of natural disasters, environmental, industrial or other disasters, to prevent accidents, etc. The main purpose of charity is to make the world a better place. An important aspect of charitable activity is its deep awareness. One of the powerful mechanisms for supporting the social activity of public organizations of citizens is the project activity of charitable foundations. It is aimed at solving certain tasks in achieving the goal, which contributes to the issue elimination. The aspects to be reflected in the project have been proposed.